2019
DOI: 10.1103/physrevb.99.085420
|View full text |Cite
|
Sign up to set email alerts
|

Valley-polarized tunneling currents in bilayer graphene tunneling transistors

Abstract: We study theoretically the electron current across a monolayer graphene/hexagonal boron nitride/bilayer graphene tunnelling junction in an external magnetic field perpendicular to the layers. We show that change in effective tunnelling barrier width for electrons on different graphene layers of bilayer graphene, coupled with the fact that its Landau level wave functions are not equally distributed amongst the layers with a distribution that is reversed between the two valleys, lead to valley polarisation of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Similar to spintronics, a main challenge in valleytronics is how to effectively control and manipulate the valley degree of freedom [24][25][26]. The valley-dependent transport and applications have been extensively studied, including the valley Hall [27] or anomalous Hall effect [28], valley-dependent AR [29] or crossed AR (CAR) [30], valley caloritronics [31], valley filter effect [32], and valley transistors [33]. For instances, Gao et al have studied the retro-AR and specular AR in the proximitized graphene/SC junction and revealed that occurrences of two ARs are determined by the spin-valley indices [29].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to spintronics, a main challenge in valleytronics is how to effectively control and manipulate the valley degree of freedom [24][25][26]. The valley-dependent transport and applications have been extensively studied, including the valley Hall [27] or anomalous Hall effect [28], valley-dependent AR [29] or crossed AR (CAR) [30], valley caloritronics [31], valley filter effect [32], and valley transistors [33]. For instances, Gao et al have studied the retro-AR and specular AR in the proximitized graphene/SC junction and revealed that occurrences of two ARs are determined by the spin-valley indices [29].…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, however, the discussed method of control allows to utilize the M X 2 materials as a magnetic channel contacts between metallic leads (the so-called two-terminal setup) to perform valley-and spin-resolved switching operations, by the analogy to the well-established concept of the spin-filter [25,26]. The described valley-spin filter received already notable consideration, initially in terms of the graphene-based systems [2,3,27,28] and later based on the discussed here M X 2 monolayers [29][30][31]. However, although mentioned above studies provide successful initial modeling of the M X 2 valley-spin filters, the in-depth discussion of the underlying transport phenomena is still absent in the literature, hampering further developments in the field.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most fundamental of these is the prevalence of stable 2D excitons with large binding energies [4][5][6] in mono-to few-layer samples. The strong optical response of excitons provides an ideal platform to explore spintronics [7,8], valleytronics [9][10][11], single-photon emitters [12][13][14], molecule-detection [15], moiré physics [16,17] and topological properties [18].…”
mentioning
confidence: 99%